2009
DOI: 10.1080/00016480802510186
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Capsicum spray in idiopathic rhinitis: a randomized prospective application regimen trial

Abstract: A significant reduction in the frequency of IR symptom was noticed in group C (4 microg/puff, three times a day for 3 consecutive days) vs controls (p=0.003). No significant difference in side effects was recorded in patients receiving Capsicum therapy with respect to controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Present conclusions, based on a search of literature from 1960 to 2010 and using 40% of 2000 articles, (personal communication), suggests the following:20.1 | Intranasal ipratropiumThis is effective for watery rhinorrhoea (level 1b; Bronsky et al234 ) 266. Topical capsaicinDesensitization reduced symptoms for several months in non-allergic, non-infectious rhinitis, NINAR [279][280][281].…”
mentioning
confidence: 97%
“…Present conclusions, based on a search of literature from 1960 to 2010 and using 40% of 2000 articles, (personal communication), suggests the following:20.1 | Intranasal ipratropiumThis is effective for watery rhinorrhoea (level 1b; Bronsky et al234 ) 266. Topical capsaicinDesensitization reduced symptoms for several months in non-allergic, non-infectious rhinitis, NINAR [279][280][281].…”
mentioning
confidence: 97%
“…Intranasal application of Capsicum spray in IR was evaluated in a randomized placebo-controlled trial. Capsicum (4 mg/puff, three times a day for three consecutive days) showed a significant reduction in the frequency of IR symptoms compared to controls [21]. …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown symptomatic improvement in patients with NAR treated with capsaicin (103,104). A published practical therapeutic approach has suggested induction of local anesthesia followed by five hourly applications of capsaicin.…”
Section: Role Of Capsaicin In the Treatment Of Ar And Narmentioning
confidence: 99%